Producing anxiety in the neoliberal university - Berg, Lawrence D.; Huijbens, Edward H.; Larsen, Henrik Gutzon (The Canadian geographer, 2016)
Key Messages This article investigates processes of neoliberalization of the academy. It argues that neoliberalism entails shifts from exchange to competition, from equality to inequality, and turns academics into human capital. It suggests that auditing systems are key mechanisms of neoliberalization that produce unhealthy levels of anxiety and stress in the academy. This paper presents a theoretical analysis of the neoliberal production of anxiety in academic faculty members in universities in Northern Europe. The paper focuses on neoliberalization as it is instantiated through audit and ranking systems designed to produce academia as a space of economic efficiency and intensifying competition. We suggest that powerful forms of competition and ranking of academic performance have been developed in Northern Europe. These systems are differentiated and differentiating, and they serve to both index and facilitate the neoliberalization of the academy. Moreover, these audit and ranking systems produce an ongoing sense of anxiety among academic workers. We argue that neoliberalism in the academy is part of a wider system of anxiety production arising as part of the so‐called “soft governance” of everything, including life itself, in contemporary late liberalism. Résumé L'anxiété suscitée par l'université néolibérale Cet article expose des réflexions théoriques portant sur l'anxiété suscitée par les universités néolibérales de l'Europe du Nord chez les membres du personnel enseignant. L'article s'intéresse particulièrement à la montée du néolibéralisme liée aux systèmes d'audit et de classement établis afin de générer un monde universitaire qui valorise l'efficacité économique et la concurrence. Nous défendons l'idée selon laquelle de puissants modes de concurrence et de classement du rendement universitaire ont émergé en Europe du Nord. Ces systèmes sont différenciés et établissent des distinctions, et servent à jauger et promouvoir le néolibéralisme dans le monde universitaire. En outre, ces systèmes d'audit et de classement suscitent un sentiment permanent d'anxiété chez les travailleurs universitaires. Nous soutenons que le néolibéralisme dans le monde universitaire s'inscrit dans un système plus large qui suscite l'anxiété et qui prend naissance dans la soi‐disant « gouvernance modérée » de tout, y compris la vie elle‐même, sur fond de libéralisme tardif.